2009
DOI: 10.1096/fj.08-119024
|View full text |Cite
|
Sign up to set email alerts
|

CD4+lymphocytes control gut epithelial apoptosis and mediate survival in sepsis

Abstract: Lymphocytes help determine whether gut epithelial cells proliferate or differentiate but are not known to affect whether they live or die. Here, we report that lymphocytes play a controlling role in mediating gut epithelial apoptosis in sepsis but not under basal conditions. Gut epithelial apoptosis is similar in unmanipulated Rag-1(-/-) and wild-type (WT) mice. However, Rag-1(-/-) animals have a 5-fold augmentation in gut epithelial apoptosis following cecal ligation and puncture (CLP) compared to septic WT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…This finding suggests that the adaptive immunity is dispensable in this context, although lymphocytes have been shown to substantially impact the proliferation and differentiation of the intestinal epithelium (41). This suggestion is based on our findings that Rag1 Ϫ/Ϫ mice raised under SPF conditions and exhibiting a physiologically mature microbiota did not have any bacteria in their MLN, liver, spleen, or lungs and that all of these mice survived oral challenge with high levels of E. coli strain Nissle 1917.…”
Section: Discussionmentioning
confidence: 62%
“…This finding suggests that the adaptive immunity is dispensable in this context, although lymphocytes have been shown to substantially impact the proliferation and differentiation of the intestinal epithelium (41). This suggestion is based on our findings that Rag1 Ϫ/Ϫ mice raised under SPF conditions and exhibiting a physiologically mature microbiota did not have any bacteria in their MLN, liver, spleen, or lungs and that all of these mice survived oral challenge with high levels of E. coli strain Nissle 1917.…”
Section: Discussionmentioning
confidence: 62%
“…The invasion of bacteria under septic conditions induces systemic inflammation and sepsis with subsequent organ failure (37,40). Importantly, the apoptosis rate of IECs is increased in patients with sepsis (41), and IEC apoptosis is crucial for mortality in CLP-induced murine sepsis (42)(43)(44)(45)(46). A recent study in C57BL/6 mice, which were also used in our experiments, showed that CD4 ϩ lymphocytes prevent IEC apoptosis and mortality after CLP (46).…”
Section: Discussionmentioning
confidence: 86%
“…Importantly, the apoptosis rate of IECs is increased in patients with sepsis (41), and IEC apoptosis is crucial for mortality in CLP-induced murine sepsis (42)(43)(44)(45)(46). A recent study in C57BL/6 mice, which were also used in our experiments, showed that CD4 ϩ lymphocytes prevent IEC apoptosis and mortality after CLP (46). Therefore, the mechanistically most important finding of the present study is that trans-signaling inhibition by sgp130Fc completely prevented sepsisinduced IEC apoptosis in the jejunum, whereas anti-IL-6 administration only led to a partial and nonsignificant reduction.…”
Section: Discussionmentioning
confidence: 99%
“…While the presence or absence of lymphocytes does not impact gut epithelial apoptosis under basal conditions, sepsis-induced gut epithelial apoptosis is significantly higher in Rag −/− mice (which lack lymphocytes) than wild type mice, suggesting that lymphocytes play an anti-apoptotic role in the gut epithelium that is unmasked in sepsis (23). Subset analysis demonstrates that CD4+ T cells are responsible for the anti-apoptotic effect of the adaptive immune system on the gut epithelium.…”
Section: Preclinical Insights Into the Role Of The Gut As The Motor Omentioning
confidence: 99%